Suicidal Obsessions in a Patient with Obsessive Compulsive Disorder: A Case Report - Faten N. Al-Zaben (Journal of King Abdulaziz University: Medical Sciences, 2023)
Obsessive-compulsive disorder is a common psychological illness characterized by recurrent intrusive thoughts, often accompanied by uncontrollable behavior. This disorder carries its own risk for suicide; however, suicidal thoughts can be a form of an obsession content of this illness. Distinguishing the difference between suicidal obsessions and accurate suicidal ideations may be under-recognized, which contribute to unnecessarily rigorous risk assessment, and subsequent interventions. This report presents one of the very few cases in literature that describes suicidal thoughts as the obsession content of obsessive-compulsive disorder patients. The present study can assist professionals evaluate a better risk assessment, and implement suitable treatment methods for patients suffering from this particular form of obsessive-compulsive disorder. Paroxetine is the choice medicine recommended for this cognitive, restructuring in the treatment of this and similar condition illnesses.